2014
DOI: 10.1002/yd.20110
|View full text |Cite
|
Sign up to set email alerts
|

Using relational developmental systems theory to link program goals, activities, and outcomes: The sample case of the 4‐H Study of Positive Youth Development

Abstract: In contemporary developmental science, relational development systems models have been used to frame the positive youth development (PYD) perspective, which posits that youth will thrive when there is alignment between their strengths and ecological resources in their context. Evidence from the 4-H Study of PYD indicates that out-of-school-time youth development programs are key ecological resources enhancing youth thriving. This chapter discusses the particular facets of youth development programs (the "Big T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 8 publications
(11 reference statements)
1
44
0
Order By: Relevance
“…Although it is not clear how best to increase family and neighborhood cohesion to have a positive effect, this work serves to facilitate the push in modern resilience science to locate the windows of opportunity that are most conducive to positive change (Masten, 2014). Clinical research and practice have begun to address these protective enhancing ecological factors through programming implementation, such as cross-age peer mentoring programs (Karcher, 2009;Lerner et al, 2014) and family-based interventions (e.g., Multisystemic Therapy; Littell, Popa, & Forsythe, 2005), but further evaluation of the efficacy of such programs is needed (Lerner, Lerner, Bowers, & Geldhof, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not clear how best to increase family and neighborhood cohesion to have a positive effect, this work serves to facilitate the push in modern resilience science to locate the windows of opportunity that are most conducive to positive change (Masten, 2014). Clinical research and practice have begun to address these protective enhancing ecological factors through programming implementation, such as cross-age peer mentoring programs (Karcher, 2009;Lerner et al, 2014) and family-based interventions (e.g., Multisystemic Therapy; Littell, Popa, & Forsythe, 2005), but further evaluation of the efficacy of such programs is needed (Lerner, Lerner, Bowers, & Geldhof, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning mental health, Patel (2005) argued that gender should also be a core component due to differential prevalence and consequences in burden and stigma. Lerner et al (2014) showed that the results of PYD intervention programs varied as a function of socioeconomic status and gender. At high levels of involvement in PYD programs, girls from lower asset neighborhoods showed higher levels of PYD, lower depressive symptoms, and less risk behavior, while these positive outcomes were observed in boys from high asset neighborhoods.…”
Section: Implications For Practicementioning
confidence: 99%
“…Benson and Scales (2009) argued that thriving represents a dynamic and bidirectional interaction between a person's competences and developmental contexts over time, which involves the stability of his or her development towards an idealized personhood. The 4-H Study in the USA provided conclusions regarding how the participation in PYD programs promoted adolescent thriving across development Lerner et al, 2014). Thus, thriving is defined as a developmental and multidimensional construct (Benson & Scales, 2009) in which different outcomes may be described at different levels, that is, at an individual level (with markers such as psychological adjustment, academic adjustment, and healthy lifestyles), but also in terms of social engagement (e.g., with family, peers, and the community).…”
Section: Introductionmentioning
confidence: 99%
“…Germinal works by Eccles and Gootman (2002), Lerner et al (2005), and others were instrumental in delineating aspects considered key to Urban Rev (2015) 47:893-913 897 PYD, including popular PYD models used in organizations such as Boys and Girls Clubs and YMCAs across the nation, such as The Five C's of PYD and the 40 Developmental Assets (Lerner et al 2011). Subsequently, concepts of PYD were extended by Lerner et al's (2005) much-analyzed 4-H Study of PYD (Lerner et al 2014), which posited that PYD could be optimized when the individual assets of youth are aligned with the assets of their environments. These varying models of PYD are not without limitations, however, especially for Black youth.…”
Section: A Review Of the Literature: Sociopolitical Development In Osmentioning
confidence: 99%